Investigating the use of mobile applications in everyday language learning - Chan, Nee Nee *; Ang, Chin Siang (Inderscience, 2017)
The development of mobile phone applications has created a multiplicity of additional affordances and new ways of learning. In particular, mobile language learning applications such as online dictionaries and Google Translate combined with the technical affordances of smartphones and tablets are creating a new relationship between mobile learners and smart devices. In this exploratory study, a mixed method research design was used to understand how youth in Malaysia use their smart devices for learning languages and to uncover the extent of these learning experiences in their daily lives. 337 participants took part in a survey of their language learning experiences using mobile learning applications. Additionally, phenomenological interviews were conducted with 12 participants over a period of four months to uncover the lived experiences of their language learning. This paper presents the preliminary findings of the study which suggest learning is serendipitous, fragmentary and purposive; dependent on function and purpose. The findings may yield new understanding that may prove useful in its implications for formal and informal learning.